Influence of composite floor slab on seismic performance of steel plate shear walls. (January 2022) - Verma, Abhishek; Sahoo, Dipti Ranjan
Abstract: Steel plate shear walls (SPSWs) consisting of unstiffened thin steel plates attached to the horizontal and vertical boundary steel elements are often used as the lateral force-resisting systems in buildings. The presence of composite floor slabs may not only alter the force demands on the boundary elements but also influence the failure mode of SPSW systems under seismic loading. This study addresses this research gap through experimental investigation of a single-story single-bay SPSW with floor slab subjected to constant gravity load and gradually increasing reversed cyclic lateral displacement. A ductile detailing of beam-column joint has been proposed as an alternative to the conventional reduced beam sections. The test specimen demonstrated a stable hysteretic response up to 5.5% story drift without significant reduction in the lateral strength. The proposed connection ensured the desired hinge mechanism and high ductility of the SPSW specimen. Additionally, numerical analysis of SPSW systems with and without composite slabs has been conducted to predict their load-resisting capacities and modes of failure under lateral loading. The presence of the floor slab increased the axial load demand on the vertical boundary element and the shear deformation demand on the horizontal boundary elements of the SPSW system. Graphical abstract: Unlabelled Image Highlights: A large-scale SPSW with composite floor slab is tested under lateral cyclic loading in presence of gravity loads. A ductile connection between HBE-to-VBE has been proposed for SPSW systems. SPSW specimen demonstrated a stable hysteretic response up to 5.5% of story drift. Proposed numerical modeling successfully predicted the lateral resistance and failure mechanisms of SPSW systems.